The efficacy and safety of anticoagulation in cerebral vein thrombosis: A systematic review and meta-analysis. Issue 169 (September 2018) - Al Rawahi, Bader; Almegren, Mosaad; Carrier, Marc
Abstract: Background: Anticoagulation with unfractionated heparin (UFH) or low molecular weight heparin (LMWH) is the mainstay for the treatment of patients with acute cerebral vein thrombosis (CVT) with or without intracranial hemorrhage (ICH). Aim: We conducted a systematic review and meta-analysis to determine the efficacy and safety of LMWH compared to UFH for the treatment of acute CVT. Methods: An electronic search of MEDLINE, Pubmed, CENTRAL and Google Scholar was performed. Randomized controlled trials (RCT) reporting on the efficacy and safety of anticoagulation for acute treatment of CVT were included. Outcomes of interest included mortality, disability, new ICH and pulmonary embolism (PE). Results: Overall, 4 RCTs were included in the meta-analysis. Two trials compared anticoagulation (UFH (N = 1) and LMWH (N = 1)) to placebo. The use of anticoagulation therapy was associated with an odd ratio (OR) for mortality and disability of 0.31 (95% confidence interval (CI) 0.07 to 1.45; p = 0.14) and 0.3 (95% CI 0.09 to 1.01; p = 0.05), respectively. Three new ICHs were observed among patients receiving placebo and no patient had a PE complication. The other two trials compared LMWH to UFH. LMWH was associated with an OR for mortality and disability of 0.21 (95% CI 0.02 to 2.44, p = 0.21) and 0.5 (95% CI 0.11 to 2.23; p = 0.36), respectively. There were no new events of ICH or PE. Conclusion: LMWH seems to be safe and effective for the management of acute CVT. Highlights: Anticoagulation is associated with fewer deaths and lower rates of severe disabilities compared to placebo in acute CVT. LMWH seemed be associated with a more favourable risk-benefit profile when compared to UFH. Anticoagulation therapy, particularly LMWH, seems to be safe and effective for the management of acute CVT.